2015
DOI: 10.1007/s00784-015-1627-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative bleeding risk for oral surgery under continued rivaroxaban anticoagulant therapy

Abstract: Oral surgeons, cardiologists, general physicians, and patients should be aware of the increased bleeding risk after oral surgical procedures. Close observation up to 1 week postoperatively is advisable to prevent excessive bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 13 publications
3
43
0
5
Order By: Relevance
“…This is in line with the findings of Clemm et al, who reported a higher bleeding rate for patients treated with VKAs than with DOACs (19). Although Hanken et al found a bleeding rate of 11.5% after minor oral surgery in patients undergoing rivaroxaban therapy (20). Interestingly, 34.6% of the participants of our study ranked the bleeding risk of LMWH therapy as very high or high.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the findings of Clemm et al, who reported a higher bleeding rate for patients treated with VKAs than with DOACs (19). Although Hanken et al found a bleeding rate of 11.5% after minor oral surgery in patients undergoing rivaroxaban therapy (20). Interestingly, 34.6% of the participants of our study ranked the bleeding risk of LMWH therapy as very high or high.…”
Section: Discussionsupporting
confidence: 92%
“…Of the six studies, one study was assessed as good quality, four were evaluated as fair quality, and one of poor quality (Table ). Risk of bias of the 21 studies was assessed using the Newcastle‐Ottawa scale: two studies received a low risk of bias score (seven stars, Miller & Miller, ; Zeevi et al., ), 16 studies received a high risk of bias score (six stars, Andrade et al., ; Berton et al., ; Caliskan et al., ; Clemm et al., ; Gómez‐Moreno et al., , ; Hanken et al., ; Kwak et al., ; Lababidi et al., ; Mauprivez et al., ; Miclotte et al., ; Miranda et al., ; Morimoto et al., ; Patel et al., ; Yagyuu et al., and five stars, Johnston, ), and three case‐series received a very high risk of bias score (one star, Abayon et al., ; Breik et al., ; Hassona et al., ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…None of the included studies was a randomized controlled trial (RCT). Nine articles were prospective case-control studies (Andrade et al, 2018;Berton et al, 2018;Caliskan, Tükel, Benlidayi, & Deniz, 2017;Clemm et al, 2016;Gómez-Moreno et al, 2016Mauprivez et al, 2016;Miclotte et al, 2017;Miranda et al, 2016), four were retrospective case-control studies (Hanken et al, 2016;Kwak et al, 2018;Lababidi et al, 2018;Yagyuu et al, 2017), and five studies were retrospective (Johnston, 2015;Miller & Miller, 2018;Morimoto, Yokoe, Imai, Sugihara, & Futatsuki, 2016;Zeevi et al, 2017) and prospective (Patel et al, 2017) observational studies, reporting data from medical records. Three studies were case-series (Abayon, Kolokythas, Siu, & Elad, 2016;Breik, Cheng, Sambrook, & Goss, 2014;Hassona, Malamos, Shaqman, Baqain, & Scully, 2018).…”
Section: Search Results and Study Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanken et al 46 (2016) recomendam que procedimentos múltiplos sejam divididos em várias sessões, a fim de reduzir o risco de sangramento, lembrando que a complexidade do procedimento é também determinada pelo fato de envolver osteotomia e/ou retalho. A incidência de hemorragia pós--operatória foi maior após extrações dentárias que envolviam retalho e/ou osteotomia 32 .…”
Section: Discussionunclassified